Menyikapi Tindak Pidana Kekerasan Dalam Rumah Tangga Pada Masa Covid 19 - Syarifuddin Syarifuddin (Fakultas Hukum universitas Islam Sumatera Utara, 2021)
AbstractLegal counseling participants in Suka Beras Village, Perbaungan District, Serdang Bedagai Regency, North Sumatra Province generally do not understand the importance of domestic violence as regulated in Article 4 of Law Number 23 Year 2004 concerning the Elimination of Domestic Violence, with the following objectives: 1 Prevent all forms of violence in household, 2. Protect victims of domestic violence, 3. Take action against perpetrators of domestic violence and, 4. Maintain a harmonious and prosperous household, so that problems arise in the village community of Suka Beras that in the house ladder is a criminal act that must be addressed and is the responsibility of the village government. Therefore, it is deemed necessary to carry out Community Service in the Village with the title